Perbandingan Nyala Efektif dan Temperatur Pembakaran antara Potongan Bambu dan Jerami pada Proses Gasifikasi dengan Isolator Glass Wool - Bahri, Saiful (2016)
ABSTRACT Biomass is one of renewable energy with great potency in Indonesia. Based on Indonesian Energy Statistic, potential of biomass energy of Indonesia achieved 434.08 GWh. Gasification is a process of thermochemical conversion of solid fuel into gas to produce inflammable gas such as CH4, H2, CO and compounds with impurity such as H2S, CO2 and TAR. The research examines biomass wastes of bamboo chips and straws in order to know their combustion temperatures and effective flames by using glass wool isolator. Gasification furnace of up-draft type was used to examine fuel combustion. The fuel was put into combustion chamber of the gasification furnace. One process of combustion needed mass of 1.2 kg. The combustion process was conducted four times for bamboo chips and four times for straws with variation of different air velocities, namely 7.6, 6.9, 5.6, and 4.7 m/s. Thermoreader was used to read temperature of combustion, then temperature produced from gasification process was read by using thermocouple installed above of the gasification reactor. Based on results of testing, bamboo chips produced higher temperature than that of straws, and the bamboo chips had better flame effectiveness than that of straws. The differences were affected by different characters and nature of the fuels, and also, different air supply into the combustion chamber.